MANAJEMEN KEPEMIMPINAN ISLAMI DALAM MENINGKATKAN KINERJA KARYAWAN DI UD IQBAL JAYA BONDOWOSO - Rahmat; Ahmad (Al-Idarah, 2020)
Leadership management is the ability of a leader to manage the organization he leads. This is done so that the organization he leads runs properly and correctly. Every business activity carried out by the company or the like must have a leader who applies leadership management The leadership management implemented at UD Iqbal Jaya is leadership management that leads to siddik, Amanah, Tabligh and Fatonah characteristics. These four characteristics are the main factors in influencing and increasing employee loyalty.